Faber Polynomial Coefficients of Classes of Meromorphic Bistarlike Functions. (4th October 2015) - Jahangiri, Jay M.; Hamidi, Samaneh G.
Abstract : Applying the Faber polynomial coefficient expansions to certain classes of meromorphic bistarlike functions, we demonstrate the unpredictability of their early coefficients and also obtain general coefficient estimates for such functions subject to a given gap series condition. Our results improve some of the coefficient bounds published earlier.